Population and Human and Social Development Part-II - Planning Commission (Planning Commission, 2000)
Basic premises of the Family Welfare Programme are: Acceptance of Family Welfare services is voluntary. Family Welfare programme will provide Integrated Maternal and Child Health (MCH) and Family Planning services Effective Information, Education and Communication (IEC) to improve awareness Ensure easy and convenient access to family welfare services free of cost.
Planning Commission (Health, Nutrition and Family Welfare Division), Government of India